2015
DOI: 10.1371/journal.pone.0134965
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Associated Fibroblasts in Stage I-IIIA NSCLC: Prognostic Impact and Their Correlations with Tumor Molecular Markers

Abstract: BackgroundCancer Associated Fibroblasts (CAFs) are thought to regulate tumor growth and metastasis. Fibroblast Activating Protein 1 (FAP-1) is a marker for fibroblast activation and by many recognized as the main marker of CAFs. Alpha Smooth Muscle Actin (α-SMA) is a general myofibroblast marker, and can be used to identify CAFs. This study investigates the prognostic impact of FAP-1 and α-SMA in non-small cell lung cancer (NSCLC) patients and correlates their expression to 105 proteins investigated in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 42 publications
3
75
2
Order By: Relevance
“…Liao et al observed that high FAP-α is associated with poor prognosis in NSCLC 6. In another cohort, Kilvaer et al found that FAP-α indicates a better patient outcome in predicting disease free survival in lung squamous cell carcinoma and adenocarcinoma 7. Our study clearly demonstrated a prognostic value of CAF density in predicting survival for lung squamous cell carcinoma, one of the most frequent subtypes of NSCLC.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Liao et al observed that high FAP-α is associated with poor prognosis in NSCLC 6. In another cohort, Kilvaer et al found that FAP-α indicates a better patient outcome in predicting disease free survival in lung squamous cell carcinoma and adenocarcinoma 7. Our study clearly demonstrated a prognostic value of CAF density in predicting survival for lung squamous cell carcinoma, one of the most frequent subtypes of NSCLC.…”
Section: Discussionsupporting
confidence: 66%
“…It was recently demonstrated that FAP-α could serve as a novel predictor for survival6 in patients with NSCLC, with high FAP-α being a marker for poor survival. Subsequently, another study investigated the role of FAP-α in squamous cell carcinoma and adenocarcinoma in lung7 and found that increased abundance of this marker protein correlates with increased disease-free survival (DFS). Hence, this contradiction in disease outcome needs further analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic value of standard markers of activated TAFs had remained ill defined in NSCLC. Thus, the prognostic value of α-SMA had remained unclear due to conflicting observations [13,14], whereas that of fibrillar collagens has not been assessed directly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little is known on the clinical relevance of standard markers of activated fibroblasts in histologic samples from NSCLC patients. Thus very few studies have examined the prognostic value of stromal alpha-smooth muscle actin (α-SMA) in lung cancer, which is the gold standard marker of fibroblast activation [12]; moreover these studies have reported contradictory results [13,14], underscoring that the prognostic value of α-SMA in NSCLC remains unclear. In addition to α-SMA, the deposition of fibrillar (type I and III) collagens is another common marker of activated fibroblasts; however, to our knowledge their prognostic value in NSCLC has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Its isolated expression does not express fibroblasts associated with cancer. Therefore, other fibroblast markers should be used, such as vimentin, fibronectin, and the FAP used in our study, which according to some authors is considered the main marker of fibroblasts [23]. …”
Section: Discussionmentioning
confidence: 99%